Direct Instruction with SAVI Learning Model to Improve Students’ Mathematical Problem-Solving Ability: A Descriptive Study - Salingkat, Suhartini; Nihayah, Elok Faik Khotun (Jurnal Pendidikan MIPA, 2022)
This research aims to describe the ability to solve the problems of students’ mathematics and through direct learners based on SAVI is expected to provide a change in the ability to solve problems of students class VII in Junior High School 6 Bualemo, especially on triangular material. This type of research is descriptive with a qualitative approach. The subjects in this study were two class VII students. The results of this study showed that students' math problem-solving abilities were still in the "low" category. The causes are: 1) difficulty identifying the problem given, 2) difficulty determining the height of the triangle, 3) difficulty in calculating, 4) difficulty puts value into the formula, and 5) difficulty in making a partition of the triangle story problem. So, based on this information, the alternative solution is to apply direct learning based on SAVI. SAVI-based hands-on learning can provide a student's math problem-solving skills change from a "low" category to a "high enough" category. This can be demonstrated by the change in the class's grade point average from 36.78 to 81.05. Keywords: Mathematical Problem Solving Skills, Triangles, SAVI. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp952-967